(untitled) (Texas Journal of Medical Science, 2025)
The article retrospectively analyzes the clinical course of hemorrhagic vasculitis in children and the characteristics of the course in children with associated pathologies. Currently, hemorrhagic vasculitis is one of the most common and frequent pathologies in the pediatric population. Its frequency is very variable and depends on the region, its level of economic development, diagnostic and statistical features. Various manifestations of hemorrhagic vasculitis clinical signs, the severity of the course of the disease, the consequences largely depend on the state of the coagulation and anticoagulation systems of hemostasis, and which organ is damaged, and kidney damage determines the probability of a severe course of the disease.